Analisis Tindak Tutur Lokusi dalam Video Kompilasi Cerita Rakyat 3in1 dari Betawi pada Channel Youtube Dongeng Kita - Putri Aji Rahayu; Laras Safitri; Asifah Salsadila; Muhammad Thoriq Akbar; Rindiati Amellia Fatikha; Wahyu Hari Winarno; Asep Purwo Yudi Utomo (STIKes Ibnu Sina Ajibarang, 2024)
As we already know, language is something that can never be separated from everyday life. One of the functions of language is communication, because humans are social creatures, communication is very important. A statement or utterance put forward by someone can be said to be a speech act. In linguistics, speech acts are included in the science of pragmatics, where there are several types of speech acts, one of which is locutionary speech acts. Locutionary speech acts are speech acts that only express meaning or state something. In this research, the author focuses more on locutionary speech acts in the video